2021
DOI: 10.3390/socsci10030089
|View full text |Cite
|
Sign up to set email alerts
|

Demographics of Sudanese University Students in Relation to Regional Conflict and Underdevelopment

Abstract: This research examines regional differences in higher education participation rates in Sudan, and their relations with socioeconomic factors related to development, such as human development index (HDI), women’s status, urban/rural, and source of income. We pay special attention to areas of Sudan where long-running conflicts exist. Two datasets are used: the 2009 National Baseline Household Survey, conducted by Sudan’s Central Bureau of Statistics; and 2016–2017 matriculating students’ data, obtained from Suda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 15 publications
(13 reference statements)
0
1
0
Order By: Relevance
“…Recent United Nations Population Fund data showed that about 39.5% of Sudanese people are between 0 to 14 years [12]. Sudan consists of 18 states (provinces), with Khartoum as the capital state [13], with an area of 22,000 km 2 , and by 2005, o cial estimates put the population of the capital city at 4.5 million, although uno cial estimates suggest a population over 7 million [14]. As shown in Fig.…”
mentioning
confidence: 99%
“…Recent United Nations Population Fund data showed that about 39.5% of Sudanese people are between 0 to 14 years [12]. Sudan consists of 18 states (provinces), with Khartoum as the capital state [13], with an area of 22,000 km 2 , and by 2005, o cial estimates put the population of the capital city at 4.5 million, although uno cial estimates suggest a population over 7 million [14]. As shown in Fig.…”
mentioning
confidence: 99%